Results of the 2nd Scientific Workshop of the ECCO (III): basic mechanisms of intestinal healing - Rieder, Florian; Ehehalt, Robert (Journal of Crohn's and Colitis, 2012)
Abstract. The second scientific workshop of the European Crohn's and Colitis Organization (ECCO) focused on the relevance of intestinal healing for the disease
Published: 01 April 2012
Gesehen am 21.06.2018